(untitled) (Jurnal IPTA (Industri Perjalanan Wisata), 2025)
This study aims to analyze the influence of tour guide knowledge, skills, and attitude on the satisfaction of domestic tourists shopping for souvenirs at Krisna Bali Bypass, one of the largest souvenir centers in Bali. Tour guides play a vital role as intermediaries between tourists and local products, significantly shaping shopping experiences. This research employs a descriptive quantitative approach with a survey method, involving 100 domestic tourists who were assisted by tour guides. The data were analyzed using multiple linear regression. The results reveal that tour guide knowledge, skills, and attitude each have a positive and significant influence on tourist satisfaction, both partially and simultaneously. Among the three variables, attitude emerged as the most dominant factor. These findings suggest that the better the competencies of a tour guide especially in terms of attitude—the higher the tourist satisfaction during shopping experiences. The study highlights the importance of improving tour guide competencies and promoting shopping tourism in Bali